“I was having an internal conflict with myself.” COVID-19 vaccination decision-making processes among pregnant women - Subasri Narasimhan; Tahira L Perry; Leslie CM Johnson (Women's Health, 2023)
Background: Vaccination serves as an efficient primary means of control for infectious diseases. However, in the case of the COVID-19 pandemic, pregnant women within the United States had the lowest rates of COVID-19 vaccination and reported the lowest intent to vaccinate. Objectives: To explore the decision-making process for COVID-19 vaccination for people pregnant during the pandemic. Design: A secondary analysis of data from a mixed-methods study that examined the impact of COVID-19 on experiences of prenatal care, birth support, and delivery in the Southern United States. Methods: This study used a descriptive phenomenological approach to thematically analyze in-depth interviews ( n  = 20) with adult women who were pregnant by January 2020 and had their prenatal care and delivery during the pandemic beginning in March 2020. The transcripts were de-identified, coded, and thematically analyzed to saturation to identify drivers of COVID-19 vaccine decision-making based on COVID-19 vaccination status and timing. Comparative analyses were conducted to assess differences in decision-making processes based on race/ethnicity and parity. Participants also completed a sociodemographic survey that included their COVID-19 vaccination status. Results: Two themes emerged, the weighing of parallel risks and priorities from different sources resulting in vaccine decisional conflict and the need to reconcile that conflict via multiple strategies. All participants weighed priorities and risks from multiple areas of their lives and described internal conflict around vaccination. Participants described tailoring decisions to household dynamics, reconciling public and private values around vaccination, and the impact of their identities on the decision-making process. While many described concerns over vaccine safety and fetal health, uniquely, many highlighted weighing the impact of prior pregnancy loss history, with some choosing other preventive measures like social distancing or mask-wearing, which they deemed less risky. Conclusion: Pregnant people make complex COVID-19 vaccination decisions, which must be considered in future vaccine messaging and advocacy for this group.